A common MET polymorphism harnesses HER2 signaling to drive aggressive squamous cell carcinoma - Li Ren Kong (Nature Portfolio, 2020)
The MET receptor is frequently activated in cancer. Here, the authors show that in head and neck and lung squamous carcinoma, a polymorphic MET variant enhances binding to HER2, resulting in activation of HER2 signalling and progression of the cancers.